O hábitus da violência no campo das relações sociocotidianas - norte do Rio Grande do Sul (1900-1945) - Freitas, Felipe Berté (2019)
This thesis has the goal of expounding the violence habitus in of social quotidian relationships, taking as its empirical basis the criminal processes from the counties of Passo Fundo, Cruz Alta and Soledade, between 1900 and 1945.The research was conducted in order to perceive how this habitus has formed and displayed in several areas of the north-south riograndense society, specially in leisure and sociable environments; in areas of economic production; in the exercise of the coercive powers from police and judiciary authorities; in the scope of political parties relationships and in the interaction among men, women, relatives and families. In a society marked by intense structural changes and by values and codes of conduct as honor, masculinity and vendetta, the tensions generated by the contradictions of this conjuncture have potentiated the configuration and the incorporation of violence as part of the daily life of individuals and social groups. Carried out by the convergence of these factors the social, cultural and judicial legitimacy of the habitus of acting in a violent way characterizes itself, since the physical and verbal agressions, murders, imprisonments and property blazes have constituted themselves as rightful ways in the solution of conflicts and also for the amplification, maintenance and repairing of the symbolic, economic and political resources from different agents in dispute. From a historiographic, theoretic and methodological point of view we have practiced a Social History of Violence, na explanatory perspective which conceives culture as part of structure. Starting from a dialogue with Law studies and, fundamentally, with the Sociology from Pierre Bourdieu, we have sought to understand what were the structural and subjective elements that have influenced individuals and social groups to incorporate the violence habitus as part of their relations in a social quotidian field.